Decolourization of textile dyes by Schizophyllum commune : an ecofriendly mycoremediation approach to treat wastewater containing textile dye effluents - Devi, Khomdram Bijoya; Malakar, Rahul; Tamang, Sangita (Academia Journal of Biology, 2025)
Synthetic dyes are extensively used in various industries, especially the textile industry, and their discharge causes severe environmental problems and is harmful to human health. Mushrooms, especially the white rot fungus, have incredible potential for biodegradation of a variety of industrial pollutants due to the presence of enzymes such as lignin peroxidase, manganese peroxidase, laccase, etc. In this study, the common split gill fungus, Schizophyllum commune, collected from the Jiribam district of Manipur, India, was employed for biodegradation/decolourization of two highly toxic and non-degradable commercially used textile dyes, Congo Red and Methylene Blue and showed positive results. The screening for the presence of ligninolytic enzymes was also performed and found to be positive. The dye decolourization study was carried out on Potato Dextrose broth medium supplemented with 0.02% of the respective dyes in 250 mL Erlenmeyer flasks. Each flask was inoculated with the mycelium plugs of each mushroom culture and incubated in stationary condition in a BOD (Biochemical Oxygen Demand) incubator at 25 ± 2 oC. For Congo Red, the dye decolourization percentage was highest on the 5th day of incubation (91.8%), while in the case of Methylene Blue, the dye decolourization percentage was highest on the 3rd day, with 77.67%. The results suggested that S. commune can effectively degrade or decolourize these dyes, showing more potential in the case of Congo Red. It paves the way for this mushroom to be used as an efficient mycoremediation tool for the treatment of wastewater containing textile dye effluents.